Functional calculus for generators of analytic semigroups of operators - Lopushansky, O.V.; Sharyn, S.V. (Carpathian Mathematical Publications, 2012)
We construct a functional calculus for generators of one-parameter bounded analytic semigroups of operators on a Banach space. The calculus symbol class consist of the Laplace image of the convolution algebra S'_+ of tempered distributions with supports in [0, ∞). Domain of constructed calculus is dense in the Banach space.